PENGEMBANGAN PSIKOMOTOR PESERTA DIDIK PADA MATERI SENI TARI MELALUI MEDIA AUDIO VISUAL DAN METODE EKSPLORASI - Dwidarti, Fera (Jurnal Teladan: Jurnal Ilmu Pendidikan dan Pembelajaran, 2021)
This study aims to determine and describe the Exploration method in improving Students' Psychomotor Development Learning in Dance Material through Audio Visual Media and Exploration Methods at SD 2 Dersalam Bae Kudus in 2020/2021 Academic Year. This research is a Classroom Action Research (PTK). This research was conducted in 2 (two) cycles, with each cycle consisting of planning, implementing actions, observing actions, and reflecting on actions. The subjects of this study were 11 grade students of SD 2 Dersalam Bae Kudus consisting of 8 male students and 3 female students. Based on the results of this Classroom Action Research (PTK), it can be concluded that the increased learning of psychomotor development for SD 2 Dersalam students on dance material through audio-visual media and exploration methods for the 2020/2021 school year, this can be seen from the motivation to take part in learning through audio-visual media. as well as the exploration method used by the teacher in accordance with the learning conditions. The results showed that from the start of the pre-cycle, the results obtained were 30% of students who could imitate animal movements, namely 3 students. Then in the action cycle 1, there was an increase from 8 students to 11 students, the percentage of 70%. In cycle II, the research was said to be complete because all students, namely 11 students, experienced an increase in imitating animal movements, namely squatting, jumping, running which were presented 100%.